PENGARUH REWARD CHART TERHADAP KEDISIPLINAN ANAK USIA 5-6 TAHUN DI KELOMPOK BERMAIN MUTIARA BUNDA KECAMATAN PEKANBARU KOTA KOTA PEKANBARU - Musliati '; Jaspar Jas; Daviq Chairilsyah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study Aims To Know How Much Influence Reward Chart Discipline Against Children Aged 5-6 Years In Playgroup (KB) Mother of Pearl City District of Pekanbaru. This research Consists Of Two Variables: Reward Chart and Discipline Children. Proposed hypothesis in this study are the following: There Effect of Reward Chart Discipline Against Children Aged 5-6 Years Playgroup In Pekanbaru Mother of Pearl City. The study involved 14 subjects, namely 5-6 years old. Methods of data collection in this study using experimental. Data analysis techniques used in this study is a partial correlation techniques using facilities assistance program SPSS 17.0 for windos.The results showed no significant positive relationship between the Reward Chart kedisplinan Against Children Aged 5-6 Years On Play Group Mother of Pearl City District of Pekanbaru. Based on the results of test results after using the difference in child discipline are 42.93 Reward Chart Reward Chart influence Against Child Discipline.Keywords: Reward Chart, Discipline